The local knowledge of the plant names and uses by Semende tribe people in Kaur District, Bengkulu Province, Indonesia - WIRYONO WIRYONO; YUSUF WANANDI; AISYAH KURNIA ILAHI; DESELINA DESELINA; GUNGGUNG SENOAJI; SISWAHYONO SISWAHYONO (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Wiryono, Wanandi Y, Ilahi AK, Deselina, Senoaji G, Siswahyono. 2019. The local knowledge of the plant names and uses by Semende tribe people in Kaur District, Bengkulu Province, Indonesia. Biodiversitas 20: 754-761. Local botanical knowledge is essential for the survival of local communities, but there is a global trend of the loss of local botanical knowledge among young generation, which causes serious concern among ethnobotanists. The objectives of this study were: (i) to document the diversity of plant species locally utilized by the people of Semende tribe in Bengkulu, Indonesia, (ii) to know the correlation between botanical knowledge and age of those people, and (iii) to test whether their knowledge was affected by gender. Data were gathered through field observations and interviews with key informants and general respondents consisting of males and females, ranging from 16 to 60 years old. The data were analyzed qualitatively and quantitatively using regression analysis and t-test. The results showed that 106 species of plants were utilized by the people of Semende tribe for 14 types of uses. The knowledge of plant species and uses was positively correlated with age, implying that the young generation lost local botanical knowledge. Men had better botanical knowledge than women. Interaction with plants was presumably the determining factor affecting botanical knowledge. Young people spent less time in gardens than the elders, and so did the women than the men. Conversely, young people spent more time enjoying electronic entertainment than the elders, and so did the women than the men. Deliberate efforts must be done to maintain botanical knowledge among young people.